In vivo association of immunophenotyped macrophages expressing CD163 with PDGF-B in gingival overgrowth-induced by three different categories of medications - Amina J. Almahrog; Lobna R.S. Radwan; Rehab R. El-Zehery; Mohamed I. Mourad; Mohammed E. Grawish (Elsevier, 2016)
Aims: This study was carried out to identify and outline the degree of relationship between immunophenotyped macrophages expressing CD163 and PDGF-B in cyclosporine-A, phenytoin, and nifedipine-induced gingival overgrowth. Methods: Eighty adult male albino rats were selected and divided into four equal groups. Group I received no treatment. Rats of groups II, III, and IV were administered cyclosporine-A, phenytoin, and nifedipine, respectively. Routine tissue processing was carried out for staining with CD163 and PDGF-B. The results of this study were analyzed statistically. Results: Group I exhibited score 0 gingival overgrowth while group II yielded score 3 with blunt and bulbous gingival crests. Rats of group III showed score 2 with knife edge and group IV revealed less pronounced gingival overgrowth and mostly the gingival crest was knife edge. Group II had the highest mean value for CD163 while group I showed the lowest value. In addition, group II had the highest mean value for PDGF-B while group I showed the lowest value. Statistically, there was an overall significant difference between the studied groups as well as between each two groups. Conclusion: Strong association exists between immunophenotyped macrophages expressing CD163 and PDGF-B in GO induced by these medications. In addition, CD163 and PDGF-B upregulated in cyclosporine-A-induced GO compared to phenytoin and nifedipine medications.